The Effectivity of Tamarillo (Cyphomandra betacea Sendtn.) Decoction Against The Growth of Candida albicans - Putu Chintya Nitiyani Santika; Janti Sudiono (Indonesian Dental Association, 2020)
Introduction: Candida albicans is an opportunistic fungus that can become a pathogen which causes candidiasis when the condition of the oral cavity is imbalanced. Tamarillo (Cyphomandra betacea Sendtn.) is a low-fat and low-calorie fruit that has high nutritional value and provides a number of micronutrients, including vitamins, minerals, and chemical compounds, such as flavonoids, terpenoids, steroids, saponins, alkaloids, and tannins. The pharmacological effects of flavonoids, tannins, and saponins are antimicrobial and anti-fungal. Objective: This study was conducted to determine the effectiveness of a tamarillo (Cyphomandra betacea Sendtn.) decoction against the growth of Candida albicans. Method: The concentrations of tamarillo decoction used in this study were 6.25, 12.5, 25, 50, and 100%. This experimental laboratory study used the well diffusion method by measuring the diameter of the inhibitory zone. Nystatin and distilled water were used as the positive and negative controls, respectively. Results: Result showed that Tamarillo has antibacterial effect against Candida albicans. The decoction of 50% tamarillo was found to be the minimum inhibitory concentration on Candida albicans. Conclusion: Starting at a 50% concentration, tamarillo decoction is an effective growth inhibitor of Candida albicans. Hence, this natural product might be applied as an adjunctive therapy for oral candidiasis. However, further studied are still needed to confirm this result.